2016
DOI: 10.1002/ps.4321
|View full text |Cite
|
Sign up to set email alerts
|

Sugar concentration in nectar: a quantitative metric of crop attractiveness for refined pollinator risk assessments

Abstract: Those involved with pollinator risk assessment know that agricultural crops vary in attractiveness to bees. Intuitively, this means that exposure to agricultural pesticides is likely greatest for attractive plants and lowest for unattractive plants. While crop attractiveness in the risk assessment process has been qualitatively remarked on by some authorities, absent is direction on how to refine the process with quantitative metrics of attractiveness. At a high level, attractiveness of crops to bees appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
2
22
0
2
Order By: Relevance
“…These values were based on the Agencies' review of the sugar content of nectars presented in the White Paper (EPA, PMRA and CDPR 2012). These data are not necessarily representative of nectar that would be collected by nectar foragers in US agroecosystems because the plant species listed were largely non-crop plants, and nectar foragers are expected to prefer flowers with high sugar content (Knopper et al 2016;Rodney and Purdy, this issue). This issue was explored in the sensitivity analysis.…”
Section: Sugar Content Of Nectar P Imentioning
confidence: 99%
See 1 more Smart Citation
“…These values were based on the Agencies' review of the sugar content of nectars presented in the White Paper (EPA, PMRA and CDPR 2012). These data are not necessarily representative of nectar that would be collected by nectar foragers in US agroecosystems because the plant species listed were largely non-crop plants, and nectar foragers are expected to prefer flowers with high sugar content (Knopper et al 2016;Rodney and Purdy, this issue). This issue was explored in the sensitivity analysis.…”
Section: Sugar Content Of Nectar P Imentioning
confidence: 99%
“…The lower limit here represents the lowest value from the Agencies' review, and the upper limit, the solubility of fructose in water at 20°C (Chen and Chou 1993). Sugar content of nectar has been reported as high as 0.84 (see review by Knopper et al 2016), and average crop load contents have been reported as high as approximately 0.65. Therefore, a higher threshold than established by the Agencies' value of 0.6 is expected based on available nectars and sugar content preferences of foragers (see review by Rodney and Purdy, this issue).…”
Section: Sugar Content Of Nectar P Imentioning
confidence: 99%
“…(2) Proportions of time spent at various levels of energy expenditure under natural conditions (e.g., flying, hovering, resting, and endothermal versus ectothermal states). (3) The distribution of sugar concentrations of nectars collected by nectar foragers, giving special consideration to crop nectar (see Knopper et al 2016). (4) For more refined assessments that account for the fate and behavior of the pesticide, it would be useful to determine the relative amounts of fresh nectar, aged honey, and water ingested.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Mensah & Kudom (2011) aktivitas kunjungan serangga penyerbuk dipengaruhi oleh perilaku kunjungan dan struktur bunga. Selain itu, karena perpindahan serangga penyerbuk dari bunga ke bunga sebagian merupakan fungsi dari kuantitas dan kualitas nektar (Knopper et al 2016) maka informasi tentang produksi nektar di dalam bunga serta jumlah bunga jantan dan betina juga perlu diketahui.…”
Section: Pendahuluanunclassified